2019
DOI: 10.1186/s12889-019-6430-0
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and substance use among women and men at the intersections of identities and experiences of discrimination: insights from the intersectionality framework

Abstract: BackgroundIntersectionality theory focuses on how one’s human experiences are constituted by mutually reinforcing interactions between different aspects of one’s identities, such as race, class, gender, and sexual orientation. In this study, we asked: 1) Do associations between intersecting identities (race and sexual orientation) and mental health (depressive symptoms) and substance use (alcohol, tobacco, and marijuana) differ between men and women? and 2) How do single or intersecting self-reports of perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 52 publications
1
53
0
Order By: Relevance
“…We also included a single item asking respondents how often they were treated unfairly based on their gender in the previous year (i.e., from January 2020-2021), which was scored using the same 6-point scale as the racial discrimination measure. This item has been used to assess gender discrimination among both men and women [17].…”
Section: Data Collection Toolmentioning
confidence: 99%
“…We also included a single item asking respondents how often they were treated unfairly based on their gender in the previous year (i.e., from January 2020-2021), which was scored using the same 6-point scale as the racial discrimination measure. This item has been used to assess gender discrimination among both men and women [17].…”
Section: Data Collection Toolmentioning
confidence: 99%
“…This is perhaps in contrast to Hall's (2019) research on male's recovery/desistance identities in which recovery often becomes the primary social component with which they guide their recovery journeys and structure their lifestyles. The intersections of disadvantage women often experience (Vu et al, 2019) and the social expectations women must juggle with regards to their social identity (Gunn & Canada, 2015) perhaps mean women experience structural limitations which may restrict the development of a primarily recovery-focused identity. It could however be argued that in fact this balance is a healthy approach to the adoption of a recovery identity, due to the multitude of meaningful activities women became engaged in.…”
Section: Social Network: Network Change Peer Support and Identity Formationmentioning
confidence: 99%
“…Since racial/ethnic minorities are more likely to be employed in health care or low-wage jobs that are considered essential during the pandemic (31,46), emerging reports indicate they are experiencing higher levels of depression and anxiety (47). Finally, although in general gender and sexual minority status among young adults is associated with increases in depression and anxiety (48,49), intersecting ethnic and sexual minority identities have been identified as an increased risk factor for depression and suicidal ideation among Latinx and Black sexual minority men and women (50)(51)(52)(53)(54) and across people of color identified as transgender females (55,56).…”
Section: Factors Contributing To Mental Health Problems Among People mentioning
confidence: 99%
“…Our study suggests this is due not only to the infection risks associated with work outside the home during this period, but to victimization by others based on social perceptions that people of color are more likely to be infected with the virus. Past research has also shown that sexual and gender minority status, medical conditions and financial insecurity have direct impact on depression and anxiety among Black, Indigenous and Latinx young adults (26,27,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(48)(49)(50)(51)(52)(53)(54)(55)(56).…”
Section: Exploratory Analysismentioning
confidence: 99%